2014
DOI: 10.1038/ncomms6002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing lithium–sulphur battery performance by strongly binding the discharge products on amino-functionalized reduced graphene oxide

Abstract: Lithium-sulphur batteries are one very appealing power source with high energy density. But their practical use is still hindered by several issues including short lifespan, low efficiency and safety concern from the lithium anode. Polysulphide dissolution and insulating nature of sulphur are generally considered responsible for the capacity degradation. However, the detachment of discharge products, that is, highly polar lithium sulphides, from nonpolar carbon matrix (for example, graphene) has been rarely st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
517
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 939 publications
(549 citation statements)
references
References 46 publications
21
517
2
Order By: Relevance
“…To overcome these challenges, various materials are employed to immobilize S for enhancing the electrical conductivity of the S electrode and preventing the dissolution of polysulfides, including carbon materials, such as carbon nanotubes,297, 298 graphene,299, 300 carbon nanofibers,301, 302 porous carbon,303, 304 and hollow carbon spheres,305 conducting polymers like polyaniline (PANI),306 polypyrrole (PPy)18, 307 and poly(3,4‐ethylenedioxythiophne)‐ poly(styrenesulfonate) (PEDOT/PSS),308 metal oxides, such as TiO 2 ,309 Ti 4 O 7 ,310 MnO 2 ,311 indium tin oxide (ITO),312 Fe 2 O 3 ,313 La 2 O 3 ,314 VO 2 ,315 V 2 O 5 ,316 MoO 3 ,316 Nb 2 O 5 ,317 and metal hydroxides including Ni(OH) 2 318 and Co(OH) 2 319, 320. Among these host materials, graphene, CNTs and carbon fibers are proved to be very efficient in fabricating flexible Li‐S electrodes 18, 157, 298, 302…”
Section: Applicationsmentioning
confidence: 99%
“…To overcome these challenges, various materials are employed to immobilize S for enhancing the electrical conductivity of the S electrode and preventing the dissolution of polysulfides, including carbon materials, such as carbon nanotubes,297, 298 graphene,299, 300 carbon nanofibers,301, 302 porous carbon,303, 304 and hollow carbon spheres,305 conducting polymers like polyaniline (PANI),306 polypyrrole (PPy)18, 307 and poly(3,4‐ethylenedioxythiophne)‐ poly(styrenesulfonate) (PEDOT/PSS),308 metal oxides, such as TiO 2 ,309 Ti 4 O 7 ,310 MnO 2 ,311 indium tin oxide (ITO),312 Fe 2 O 3 ,313 La 2 O 3 ,314 VO 2 ,315 V 2 O 5 ,316 MoO 3 ,316 Nb 2 O 5 ,317 and metal hydroxides including Ni(OH) 2 318 and Co(OH) 2 319, 320. Among these host materials, graphene, CNTs and carbon fibers are proved to be very efficient in fabricating flexible Li‐S electrodes 18, 157, 298, 302…”
Section: Applicationsmentioning
confidence: 99%
“…However, the insulating nature of sulfur (S) and its reaction products (i.e., Li 2 S), the large volume expansion from S to Li 2 S, along with the dissolution of lithium polysulfide intermediates (i.e., Li 2 S x , 4 ≤ x ≤ 8) into liquid electrolyte and the consequent shuttling effect between the anode and cathode, makes it generally display poor rate ability, limited cycle life and severe self‐discharge 1, 2, 3, 4, 5, 6, 7. Therefore, a variety of strategies have been pursued to circumvent the sulfur cathode problems, including optimization of organic electrolytes8, 9 and fabrication of sulfur‐conductive polymer composites10, 11 and sulfur–carbon‐based composites 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45. Among these approaches, porous‐carbon/sulfur composites12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 are more attractive because porous carbon can i...…”
Section: Introductionmentioning
confidence: 99%
“…According to their report, strong chemical interaction between S and the functional groups on GO happens and S can partially reduce the GO. Especially, according to very recent investigations,41, 46 the hydrophilic surface groups of GO should be quite important for immobilizing the hydrophilic lithium polysulfide intermediates. Furthermore, GO network can also accommodates the volume change of the electrode during the Li–S electrochemical reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cathode modification is a common method to effectively sequester LiPS by incorporating affinity additives. Graphene oxide,16, 17 metal oxides/sulfides,18, 19, 20, 21 polymers,9, 22, 23 and bifunctional binders24, 25 have been widely studied to constrain active cathode materials by the high binding energy between sulfur species and O,N‐containing functional groups. These studies have indicated that stronger interactions between the polar group from the conductive materials (e.g., oxides and sulfides) and the S species enable better confinement of Li 2 S x and enhance the cycling performance of an Li–S cell.…”
mentioning
confidence: 99%